JOSHUA 24 AND THE WELCOME OF FOREIGNERS - D G Firth (Acta Theologica)
Although the book of Joshua is often read as being hostile to non-Israelites, this paper argues that its concern is not with ethnicity but rather with the nature of someone’s relationship to Yahweh. Understood against the wider narrative arc of the book, Joshua 24 thus becomes the point where this is explored in full. This then establishes a pattern that runs through the Former Prophets which consistently demonstrate the possibilities for foreigners within Israel. The means by which this is presented suggest that Joshua in particular is arguing against a dominant social model which is opposed to foreigners. From this, it can be seen that Joshua is establishing an ethical paradigm which is welcoming to those who commit to Yahweh.